Requiem - Tangen, Geir, 1970- (Minotaur Books, 2018)
"Journalist Viljar Gudmundsson is no stranger to chilling stories. So when he receives an anonymous e-mail in which the writer proclaims their intention to execute a woman for her unpunished crimes, he thinks the whole thing is a bad joke. Such things happen only in bad crime novels, after all. But the next day, the body of a woman is found, and Viljar receives a second e-mail with another verdict from this self-proclaimed judge, jury, and executioner. Viljar joins forces with Investigator Lotte Skeisvoll, who quickly realizes that the murderer is playing a deadly game with them. The clues are all pointing in the same direction, and the murders are strangely familiar..."--